THE MOTIVATIONAL IMPACT OF AUGMENTED REALITY ON ARCHITECTURE STUDENTS: A FIELD STUDY AT AN INTERNATIONAL EXHIBITION - Amokrane Radhwane; Gherzouli Lazhar; Atef Ahriz; Lousfane Selma (International Journal of Innovative Technologies in Social Science, 2024)
This study aimed to evaluate the effectiveness of augmented reality technology in motivating architectural engineering students and improving their comprehension of complex projects. An AR- application called "builtec" was developed, displaying two architectural models: an exterior view of the building and its surroundings, and an interior view showing the internal details of one floor. The study adopted an experimental analytical approach, conducting the experiment using modern digital and tablet devices on a sample of 81 students during an international exhibition held in Algeria in 2024. Results showed significant success of the technology, with the attractiveness of the experience receiving a strong approval rate of 95%, interaction with the virtual model achieving 86% approval, and ease of technology use reaching 82%, along with positive technical aspects evaluation at 92%. The study concluded by demonstrating the effectiveness of augmented reality technology as a means to increase interaction, motivation, and enhance architecture students’ understanding of complex projects. The study recommends expanding the use of augmented reality technology in educational curricula and conducting more comparative studies covering various architectural presentation techniques to identify the best technologies and practices in architectural education.